Image-Guided Focused Ultrasound-Mediated Regional Brain Stimulation in Sheep - Lee, Wonhye; Lee, Stephanie D.; Park, Michael Y.; Foley, Lori; Purcell-Estabrook, Erin; Kim, Hyungmin; Fischer, Krisztina; Maeng, Lee-So; Yoo, Seung-Schik (ELSEVIER SCIENCE INC, 2016)
Non-invasive brain stimulation using focused ultrasound has largely been carried out in small animals. In the present study, we applied stimulatory focused ultrasound transcranially to the primary sensorimotor (SM1) and visual (V1) brain areas in sheep (Dorset, all female, n = 8), under the guidance of magnetic resonance imaging, and examined the electrophysiologic responses. By use of a 250-kHz focused ultrasound transducer, the area was sonicated in pulsed mode (tone-burst duration of 1 ms, duty cycle of 50%) for 300 ms. The acoustic intensity at the focal target was varied up to a spatial peak pulse-average intensity (Isppa) of 14.3 W/cm(2). Sonication of SM1 elicited electromyographic responses from the contralateral hind leg, whereas stimulation of V1 generated electroencephalographic potentials. These responses were detected only above a certain acoustic intensity, and the threshold intensity, as well as the degree of responses, varied among sheep. Post-sonication animal behavior was normal, but minor microhemorrhages were observed from the V1 areas exposed to highly repetitive sonication (every second for >= 500 times for electroencephalographic measurements, Isppa = 6.6-10.5 W/cm(2), mechanical index = 0.9-1.2). Our results suggest the potential translational utility of focused ultrasound as a new brain stimulation modality, yet also call for caution in the use of an excessive number of sonications. (C) 2016 World Federation for Ultrasound in Medicine & Biology.